The 100 top-cited studies in systemic lupus erythematosus: A bibliometric analysis - Liuliu Quan; Jiawen Dai; Yuan Luo; Lin Wang; Yue Liu; Jiaqi Meng; Fan Yang; Xin You (Human Vaccines & Immunotherapeutics)
Systemic lupus erythematosus (SLE) is an autoimmune inflammatory tissue disease. In view of the explosive growth in research on SLE, bibliometrics was performed to evaluate the 100 top-cited papers in this realm. We performed the search with terms “systemic lupus erythematosus” the Web of Science Core Collection database on May 3, 2023. Relevant literatures were screened. Data were extracted and analyzed by SPSS. The citations of 100 top-cited SLE studies spanned from 472 to 13,557. Most studies (60 out of 100) were conducted in the United States. Total citation times were positively associated with ACY, which was negatively correlated with the length of time since publication. Approximately half of the studies focused on the underlying mechanisms of SLE. New biologic therapies garnered attention and development. Our findings provide valuable insights into the developments in crucial areas of SLE and shed contributions to future studies.